Veronika decides to die - Coelho, Paulo (HarperCollins Publishers, 2017)
"Another of Coelho's spiritual journeys, this time by the 24-year-old protagonist who, after a failed suicide attempt, rediscovers in an insane asylum in Slovenia the preciousness and precariousness of life. Costa's translation is competent, but cannot save Coelho's novel from its by now familiar and conventionally inspirational tone and message"--Handbook of Latin American Studies, v. 58.